Differential stimulation of muscle protein synthesis in elderly humans following isocaloric ingestion of amino acids or whey protein - Paddon-Jones, Douglas; Sheffield-Moore, Melinda; Katsanos, Christos S.; Zhang, Xiao-Jun; Wolfe, Robert R. (Experimental gerontology, 2006)
To counteract the debilitating progression of sarcopenia, a protein supplement should provide an energetically efficient anabolic stimulus. We quantified net muscle protein synthesis in healthy elderly individuals (65–79 yrs) following ingestion of an isocaloric intact whey protein supplement (WY; n=8) or an essential amino acid supplement (EAA; n=7). Femoral arterio-venous blood samples and vastus lateralis muscle biopsy samples were obtained during a primed, constant infusion of L-[ring- 2H 5]phenylalanine. Net phenylalanine uptake and mixed muscle fractional synthetic rate (FSR) were calculated during the post-absorptive period and for 3.5 h following ingestion of 15 g EAA or 15 g whey. After accounting for the residual increase in the intracellular phenylalanine pool, net post-prandial phenylalanine uptake was 53.4±9.7 mg phe leg −1 (EAA) and 21.7±4.6 mg phe leg −1 (WY), ( P<0.05). Postabsorptive FSR values were 0.056±0.004% h −1 (EAA) and 0.049±0.006% h −1 (WY), ( P>0.05). Both supplements stimulated FSR ( P<0.05), but the increase was greatest in the EAA group with values of 0.088±0.011% h −1 (EAA) and 0.066±0.004% h −1 (WY), ( P<0.05). While both EAA and WY supplements stimulated muscle protein synthesis, EAAs may provide a more energetically efficient nutritional supplement for elderly individuals.